Peran Mahasiswa Dalam Peningkatan Kualitas Literasi Sebagai Wujud Pengabdian Kepada Masyarakat Di Desa Tajinan Kabupaten Malang - Citra Ayu Winie Febrianti; Irfan Arya Widya; Hayyu Imtiyaz; Sarah Maryam Hafidza; Rahmah Alia Handini; Tabitha Hosianna Hutagaol; Najma Athala Kayyisa; Nayla Azzahra Hanggita; Cut Tera Cantika; Muhammad Annas Satria; Dian Novita Dewi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
This community service program was conducted to improve children's literacy skills in Tajinan Village, Malang Regency through various engaging educational activities. The main problems identified were low reading interest among children and lack of parental understanding about the importance of literacy for their children's future. The method used was a participatory approach where students collaborated with the community, youth organizations, and teachers during the period of July 9 to August 7, 2025. The main programs implemented included awareness of the prominent of literacy, a literacy competition entitled "Gema Literasi Anak (Literacy Awareness for Children)" comprising poems on local culture, education on the prevention of sexual violence and bullying, basic English courses, educational film screenings, social media content training for youth organizations, and waste management workshops. Program results showed high enthusiasm from children with active participation in every activity, increased reading interest, and development of their creativity in writing poetry about local folklore. The program also successfully raised high school students' awareness about the importance of continuing higher education and developed digital literacy skills among young villagers. Positive impacts were impacted not only by children but also by parents who began supporting literacy activities at home. In conclusion, university students proved to be effective bridges between the academic world and rural communities in building sustainable literacy culture.